Didactic Strategy for Learning Theory of Automata & Formal Languages: Didactic Strategy for Learning Automata - Naveed, Muhammad Shumail; Sarim, Muhammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Formal languages and automata theory have a strong association with the core of information in the area of computer science. However, the courses on formal languages and automata theory is a challenging task and students generally do not find these courses very attractive and experience intricacy and impediment in learning the concepts. These intricacies stem from the difficult and unusual abstract concepts and the essential mathematical background. This paper presents a didactic strategy to simplify the hardness of the courses on formal languages and automata theory and aids to increase the interest and commitment of students in these courses. The proposed strategy supports a more imperative learning of the topics in formal languages and automata theory in an effective and fruitful way. The strategy initially evaluated and primary results are quite encouraging.